Digital tools in language teaching: a systematic review of pedagogical impacts, AI innovations, and sociocultural competence - Abdul Halim, Rosmani; Sahrir, Muhammad Sabri; Abdullah, Nurazzelena; Abd. Rahman, Siti Fatimah (AMRASS Press, 2025)
This systematic literature review examines the integration of digital tools in language teaching, focusing on their pedagogical implications, effectiveness, and socio-cultural impacts across diverse educational contexts. The study synthesizes empirical research from 46 peer-reviewed articles (2021– 2025) to address three key questions: (1) the pedagogical implications of digital tool integration, (2) the role of AI and intelligent tools in language learning, and (3) the contribution of digital tools to sociocultural and intercultural competence. Adhering to PRISMA guidelines, the review employs thematic analysis to identify trends and gaps in the literature. Key findings reveal that digital tools enhance language acquisition, multimodal literacy, and student engagement, with AI-driven tools like chatbots and ChatGPT offering personalized learning but raising ethical concerns. Teacher digital competency and professional development emerge as critical for effective implementation, while socio-cultural applications, such as digital storytelling, foster intercultural awareness. Challenges include inequitable access, data privacy, and the need for culturally relevant pedagogies. The study underscores the transformative potential of digital tools in language education while advocating for balanced, ethical, and context-sensitive integration. Implications for educators, policymakers, and researchers include prioritizing teacher training, equitable resource distribution, and further exploring scalable models. This review contributes to evidence-based strategies for optimizing digital language teaching in primary to tertiary settings.